The challenges of creating an online undergraduate community of practice. (13th April 2015) - List, Sarah S.; Warland, Jane; Smith, Colleen
Abstract : Purpose: – With less time spent on campus, students are increasingly forming peer friendship and study groups either face to face or online. Communities of practice (CoP) with academic support in the wings could benefit students, but little is known in the about their use in the undergraduate space, or how best they may be structured and facilitated (Andrew et al., 2008). The purpose of this paper is to discuss these issues. Design/methodology/approach: – An online CoP was created in partnership with undergraduate bachelor of midwifery students at the University of South Australia using an action research model. This provided an ongoing ability to continuously plan, act, observe and evaluate all aspects of the community created, so that adjustments could be made during the two cycles of the study. Findings: – The time paucity of the cohort impacted on their ability to participate fully as partners in the project, and in the community itself. The Facebook community received more visitation than the Weebly community. The student panel reported that despite the online CoP fitting better with their schedules, they would prefer more opportunities to interact face to face with their peers. Research limitations/implications: – Students who spend limited time on campus may prefer more real life social contact and support, despite the convenience of an online community. A larger cohort, drawing from a non-professional degree would have allowed greater membership and community participation for a prospective study such as this. Practical implications: – Remote study is a growing phenomenon, and students need to feel socially connected and supported to remain enroled and engaged. Social implications: – There has been much discussion around the amount of time individuals spend online, and whether support groups formed by students on social media support student learning, or encourage unprofessional behaviours without academic support present. Originality/value: – This study reports that online communities are not always a logical solution to time poor students, and they may prefer face to face interactions to build their social and professional relationship.